Measuring consumption over the phone: Evidence from a survey experiment in urban Ethiopia - Abate, Gashaw T.; de Brauw, Alan; Hirvonen, Kalle; Wolle, Abdulazize (United Nations University, 2022)
The paucity of reliable, timely household consumption data in many low- and middle-income countries has made it difficult to assess how global poverty has evolved during the COVID-19 pandemic. Standard poverty measurement requires collecting household consumption data, which is rarely done by phone. To test the feasibility of collecting consumption data over the phone, we conducted a survey experiment in urban Ethiopia, randomly assigning households to either phone or in-person interviews. In the phone survey, average per capita consumption was 23 per cent lower than in the in-person survey, and the estimated poverty headcount was twice as high. There is evidence of survey fatigue occurring early in phone interviews but not in in-person interviews; the bias is correlated with household characteristics. While the phone survey mode provides comparable estimates when measuring diet-based food security, it is not amenable to measuring consumption using the ‘best practice’ approach originally devised for in-person surveys.